Kansas PRIDE Program 2012-13 Program Recognition - Rice, Trudy; Menon, Jaime (My University, 2014)
Summary of the 2013 actiivities of the Kansas PRIDE program and affiliated communities.
Keywords: Administrative and Research Reports; Community Development